The Wave Energy Up Conversion of Plasma Wave in Inhomogeneous Ionosphereic Plasma: The Wave Energy Up Conversion of Plasma Wave - Deka, P. N.; Gogoi, S. (Journal of Scientific Research, 2019)
Different types of instabilities are observed in the thermodynamically nonequilibrium Earth's ionosphere. Effective energy exchange process among waves may takes place through nonlinear interaction modes because of availability of free energy. We consider gradients in density and magnetic field is present in the system which support drift wave turbulence. In this study we concern on the wave energy up conversion of electrostatic nonresonant lower hybrid wave through plasma maser instability in the mid-altitude ionospheric region. We have formulated the growth rate of lower hybrid wave by Vlasov-Poisson mathematical frame and estimated its value by observational data.